PENGALAMAN AUDIT SEBAGAI EKSPLANASI PERTIMBANGAN AUDITOR DENGAN MODERASI KREDIBILITAS KLIEN - Santosa, Made Edy Septian; Ramantha, I Wayan; Badera, Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Factor that can influence the judgment auditors evaluate evidence in an audit, among which are the auditors experience. But often the auditor is a difficult situation to determine when the credibility of the judgement of the client. This research was to obtain empirical evidence on the effect of audit experience on the effect of auditor’s judgement that further moderated client credibility. The testing of hypotheses in this research was done using analysis test interaction Moderated Regression Analysis (MRA). The hypotesis testing showed that audit experience have positive relationship to judgment auditor. While moderating influence is significant client credibility and strengthen the positive effect on the judgment auditor's of audit experience.
Keywords: Pengalaman Audit; Pertimbangan Auditor; Kredibilitas Klien